FAO food and nutrition paper; No.62 - FAO (FAO, 1997)
The book covers past experiences and needs for nutrition education; a framework for nutrition education programmes; nutrition education and communication strategies for different groups and settings; training needs for nutrition eduction; evaluation of nutrition eduction programmes; and new developments in computer-mediated technology for nutrition education